Specific design and assessment of the development of the social capital of the regions of Ukraine - Петряєв, О. О.; Грузд, М. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The article deals with the problems of formation and evaluation of social capital in the system of human development priorities. The lack of scientifically grounded concepts and models of social capital management in Ukraine was proved. The approaches to the interpretation of the essence of the social capital of the region and the country were generalized. The main features of the concept under consideration were determined. It is shown that social capital consists of the elements that directly determine the social activity of the population of the region and the level of its social security. It is substantiated that the social capital of the region is made up of the capacity of individuals and the corresponding prerequisites, which together create a new entity. The priority of the social component of development of social capital of the region is determined. The specific feature of the social capital of the region and the levels of its design are revealed. The main indicators affecting the development of the regional social capital are named. The structure of indicators is presented and the main characteristics of the social capital of the region are given. The initial provisions concerning the transformation of the social capital of the region into a social resource are substantiated and mechanisms for activating these processes are defined. The stages of estimating the social capital of the regions of Ukraine are shown and their content is disclosed. The social capital of Ukrainian regions is estimated in dynamics. Measures to overcome the uneven development of regions of Ukraine are proposed. It is recommended to use stimulating measures to revitalize the social capital of the regions of Ukraine on the basis of an effective mechanism of public administration. The need for ensuring the financial autonomy of the regions by delimitating competence between state authorities, local self-government and economic entities is justified. It is proposed to develop a mechanism of interregional cooperation.